Guideline for Developing a Model of Prevention of the Problem of Elder Abuse in Communities of Thailand - Rattanarat, Nirumon (Journal of Contemporary Social Sciences and Humanities, 2025)
The research aimed at surveying information about the elder abuse situation in Nang Rong district, Buriram province, Thailand and studying ways of prevention of the elder abuse in the community of Nang Rong Municipality Buriram Province, Thailand for developing it as a model of good practice to be used in other community areas. The research was carried out by mixed methods research including both quantitative and qualitative. Sample size included 351 elders residing in communities of Nang Rong Town Municipality, Nang Rong district, Buriram province, Thailand. The quantitative research utilized Krejcie and Morgan table for determining sample size of a given population. Its research tool was questionnaires. Derived information was then analyzed by statistical method that includes percentage and mean. In addition, qualitative research was also carried out by in-depth interview and focus group discussion among related state officials and private sectors. The research resulted ways of prevention of the elder abuse in the Nang Rong Municipality community Buriram Province could be used as a good practice to guide other community areas. These following actions should be done in the community i.e. elder abuse prevention through social development by raising public comprehension about nature of elder abuse and means of elder abuse prevention and providing neighborhood watch and citizen patrol, community or locally-based elder abuse prevention by applying concept of the neighborhood care, setting up a committee by local government organization or municipality to be in charge of monitoring or preventing recidivism and providing assistance to any abused elder as well as a use of community justice system in dispute resolution.